Pengaruh Gear Ratio pada Motor BLDC Mid Drive 2 kW terhadap Kinerja Sepeda Motor Listrik Konversi - Fuad Adhi Prasetya; Budi Basuki; Benidiktus Tulung P.; Agustinus Winarno; Daniel Janthinus Kristianto (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
The reduction of carbon dioxide emissions, or decarbonization, across all sectors must be carried out seriously. One of these sectors is transportation, through the implementation of an electric vehicle (EV) ecosystem by converting fossil-fuel-powered motorcycles into electric motorcycles. This study aims to design and analyze the performance of a 2 kW mid-drive BLDC motor in an electric motorcycle conversion application. The transition to electric vehicles requires conversion components, such as a BLDC motor. A collaborative research project with an industrial partner, PT X, focuses on the design and modification of a 2 kW mid-drive type BLDC motor. The design process was carried out by varying the gear ratios of 0.68, 0.72, and 1.34 to obtain an electric motorcycle conversion speed suitable for urban road use. Dynotest results indicate that the gear ratio variation of 0.68 provides the best performance using 30T and 20T gears. The maximum speed achieved under this configuration was 78.8 km/h, with a torque of 24.18 Nm at 987 rpm and an output power of 2.8 kW at 1526 rpm.